Scientific chairs of Iraqi universities and their role in achieving sustainable development goals - Rawaa Hussein Mohammed; Mustafa Salim Abed Bkeet (Journal of Legal Sciences, 2024)
The study aims to show the emergence of UNESCO chairs in Iraqi universities and the activities carried out to achieve the goals of sustainable development, as each chair was established to achieve one of these goals, which left its impact on some educational and social sectors, and thus the importance of the study emanates from the need to indicate the establish of UNESCO chairs in Iraqi universities and the activities that strengthened their establishment, activity and local and international initiatives, as well as to identify what these chairs have achieved from the sustainable development goals.